NILAI STRATEGIS ALIANSI INDONESIA DENGAN AMERIKA SERIKAT DALAM PENGAMANAN BLOK LAUT AMBALAT - Yani, Yanyan M.; Montratama, Ian (Pusat Penelitian Politik, 2015)
In globalization era, great powers pose more intense and wider influence toward other lesser states in the globe. Theoritically, Walt argues that medium and lesser states tend to align toward greater powers to have protection against threat. However, in practice, Indonesia keeps standing to become a neutral state that does not ally to any power blocks. This paper will examine the benefit for Indonesia to ally with the United States OF America in a case of securing the trouble water in Ambalat Sea Bloc.Keywords: globalization, great power, medium state, quasi-alliance, Ambalat Sea Bloc.